Serving Through Knowledge: Educational Community Service For A Better Future In Stit Al-Ittihadiyah Labuhanbatu Utara - Vera Asihna Riris Pasaribu (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2024)
Educational community service programs have become an essential avenue for bridging academic knowledge and community development. This study explores the implementation and impact of such programs at STIT Al-Ittihadiyah Labuhanbatu Utara, focusing on how they empower local communities and contribute to a better future. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving students, lecturers, and community members. The findings reveal that these programs enhance educational engagement, develop practical skills, and foster social cohesion, benefiting both the community and student participants. However, challenges such as limited resources and inconsistent community involvement affect program sustainability. The study highlights the importance of strategic planning and collaborative efforts to maximize the positive outcomes of educational community service. Ultimately, serving through knowledge proves to be a powerful means of fostering community empowerment and sustainable development.